Respuesta :
Answer:
The point-slope form:
[tex]y - y_1 = m\;(x - x_1)[/tex].
The inputs are:
- [tex]y_1 = -2[/tex],
- [tex]x_1= -11[/tex], and
- [tex]m = -2[/tex].
The equation of the line in point-slope form will be:
[tex]y {\bf + 2} = {\bf -2} \;(x {\bf+11})[/tex].
Step-by-step explanation:
Why the point-slope form?
Prefer this form in case both of the following are given:
- The coordinates of a point on the line, and
- The slope (a.k.a. gradient) of the line.
What is the equation of a line in the point-slope form?
[tex]y - y_1 = m(x - x_1)[/tex],
where [tex]x[/tex] and [tex]y[/tex] are variables. The point-slope form takes three parameters:
- [tex]x_1[/tex], the x-coordinate of the given point;
- [tex]y_1[/tex], the y-coordinate of the given point; and
- [tex]m[/tex] the slope of the line.
The coordinate of the given point on the line is
[tex](\underbrace{-11}_{x_1}, \underbrace{-2}_{y_1})[/tex].
In other words,
- [tex]x_1 = -11[/tex], and
- [tex]y_1 = -2[/tex].
The slope of the line is -2. As a result,
- [tex]m = -2[/tex].
Hence the equation:
[tex]y - (-2) = -2\;(x - (-11))[/tex]
[tex]y + 2= -2\;(x + 11)[/tex].